The Role of the Key Effector of Necroptotic Cell Death, MLKL, in Mouse Models of Disease - Emma C. Tovey Crutchfield (Biomolecules, 2021)
Necroptosis is an inflammatory form of lytic programmed cell death that is thought to have evolved to defend against pathogens. Genetic deletion of the terminal effector protein—MLKL—shows no overt phenotype in the C57BL/6 mouse strain under conventional laboratory housing conditions. Small molecules that inhibit necroptosis by targeting the kinase activity of RIPK1, one of the main upstream conduits to MLKL activation, have shown promise in several murine models of non-infectious disease and in phase II human clinical trials. This has triggered in excess of one billion dollars (USD) in investment into the emerging class of necroptosis blocking drugs, and the potential utility of targeting the terminal effector is being closely scrutinised. Here we review murine models of disease, both genetic deletion and mutation, that investigate the role of MLKL. We summarize a series of examples from several broad disease categories including ischemia reperfusion injury, sterile inflammation, pathogen infection and hematological stress. Elucidating MLKL’s contribution to mouse models of disease is an important first step to identify human indications that stand to benefit most from MLKL-targeted drug therapies.